Literackie inscenizacje Georges’a Pereca - Woźniak-Czech, Ewelina (Przestrzenie Teorii, 2017)
The purpose of this sketch to present Georges Perec’s work in the context of drama. As Perec wrote just one play for the theater, it’s hard to call him a dramatist. However, it is easy to see that all the literary tricks he uses in his works are a part of a well-thought-out game. The author of Life a User’s Manual employs and interweaves various literary conventions, prompts dialogue between his own works and draws the reader into the very center of his tricks, nuances and simulations. Perec’s writing could be deemed a pure act of dramatization, where the author himself, to some extent, takes on the role of director, making his audience not so much the recipients of his texts but the actors performing them.